The effect of e-service quality dimensions on BCA mobile user satisfaction at PT. Bank Central Asia, Tbk KCU Palembang - Setyowidodo, Yohannes; Wahab, Zakaria; Shihab, Muchsin Saggaf; Widiyanti, Marlina (International research journal of management, IT and social sciences, 2021)
This study aims to determine the effect of the dimensions of e-service quality, including efficiency, fulfillment, system availability, privacy, responsiveness, and contact, on the decisions of BCA Mobile users at PT. Bank Central Asia, Tbk. The population in this study were all K1 customers focused on individual BCA Mobile service users in the period 2019-2020 at PT. Bank Central Asia, Tbk KCU Palembang, totaling 1,203 customers. The sample in this study was 112 customers obtained through a purposive sampling technique with the criteria of respondents being taken as samples were K1 Individual Focus customers who used BCA Mobile services in 2019-2020. The data collection method used a questionnaire distributed to all consumers, and the data was processed using multiple linear regression analysis. The results of multiple linear analyses show that efficiency, fulfillment, system availability, privacy, responsiveness, and contact have a positive and significant impact on customer satisfaction using BCA Mobile at PT. Bank Central Asia, Tbk. The BCA Mobile application makes it easy for customers to carry out their banking transactions anytime and anywhere independently.